Cr(III),Mn(II),Fe(III),Co(II),Ni(II),Cu(II) and Zn(II) Complexes with Diisobutyldithiocarbamato Ligand - Mohammad Tarique (E-Journal of Chemistry)
The synthesis of sulphur and nitrogen containing dithiocarbamato ligand derived from diisobutylamine as well as its coordination compounds with 3d series transition metals is presented. These synthesized compounds were characterized on the basis of elemental analysis, conductometric measurements and IR spectral studies. The analytical data showed the stoichiometry 1:2 and 1:3 for the compounds of the types ML2 {M=Mn(II), Co(II), Ni(II), Cu(II) and Zn(II)} and M'L3{M'=Cr(III) and Fe(III)} respectively. The conductometric measurements proved the non-electrolytic behaviour of all the compounds. The bidentate nature of dithiocarbamato moiety was confirmed on the basis of IR spectral data.